Economic downturns shape employee reward preferences - SIROLA, Nina (Institutional Knowledge at Singapore Management University, 2016)
This research tests the idea that preferences for performance-based pay inequality are shaped by economic cycles. We study this phenomenon from the perspective of both key actors relevant to employee rewards--employees and employers. Study 1 used data from 77,644 employees and 24,435 employers coming from 78 countries and sampled across 17 years, and found that worse economic periods were associated with preferences for higher levels of performance-based pay inequality among both employees and employers. Subsequent studies used a novel experimental approach to manipulate the perception of the economic environment, replicating the effect among both employees (Study 2) and employers (Study 3), and testing the psychological process and boundary conditions. Taken together, this research provides a novel explanation for organizational members' reward distribution preferences and thus demonstrates the importance of bridging the macro-micro divide in organizational sciences by conceptualizing individual decision making in the context of a changing macroeconomic environment.